Severe hepatitis B reactivation during direct-acting antiviral treatment in "the absence" of hepatitis B surface antigen. (February 2019) - Sastre, Lydia; Ruiz, Pablo; Costa, Josep; Forns, Xavier
Highlights: We present a case of HBV reactivation in a kidney transplant patient treated with direct acting antivirals in the setting of chronic HCV infection. Direct acting antiviral therapy should be considered as a potential cause of HBV reactivation in patients undergoing DAA therapy. Sensitivity of HBsAg diagnostic tests is low in individuals with HBsAg escape mutants. HBV DNA determination should be part of the laboratory work-up in immunosuppressed patients with HBV infection and liver test abnormalities. Abstract: Hepatitis C virus (HCV) treatment with direct-acting antivirals (DAA) can be associated with reactivation of hepatitis B (HBV). We report a case of a kidney transplant recipient who had a fatal severe HBV reactivation during treatment for chronic hepatitis C with DAA. Diagnosis of HBV reactivation was delayed due to undetectable surface antigen (HBsAg) by standard assays. The latter was explained by the presence of HBsAg escape mutants. The case illustrates the relevance of HBV-DNA testing in transplant recipients with previous exposure to HBV, even in the absence of HBsAg, and particularly when liver test abnormalities are present.